AGA662: Research Project II / Faculty of Plantation and Agrotechnology - UiTM, Faculty of Plantation and Agrotechnology (Universiti Teknologi MARA (UiTM), 2020)
This course requires a final year students to carry out a project of their proposed under supervision of one or two lecturer in related area in the faculty or university. The data of their research need to be analyze using specific software and the results need to be discussed. The project outcomes must be presented in written form and submitted to the supervisor(s) and examiners. Oral presentation and project report will be evaluated. The commitment, discipline and creativity of the student in conducting the project, data collection, data analysis, discussion and concluding the project will also be assessed